Visitors' guide to the Philippines your comprehensive travel companion to exploring the Philippines. (Makati City Integrated Marketing Services (Phils) Inc., 1997)
This guide for tourists and visitors to the Philippines. As with other tourist guidebooks, it lists establishments and tourist destinations, with color illustrations. Included are essays and contact information on accomodations, shopping, business, wining and dining, nightlife and entertainment, resorts, arts and culture, and sports. It has features on Metro Manila tourists and visitor's activities as well as daytrips to places of interest near Metro Manila. It has a special feature on the Philippine centennial celebrations and Philippine flora and fauna. A unique feature is the index, which is listed in seven languages: English, Filipino, Japanese, Chinese, French, Spanish and German.
Keywords: Philippines -- Description and travel -- 1986- -- Guidebooks